Examining Specialization and Diversification of Manufacturing Industries on Regional Economic Resilience in Indonesia - Amin, Wisnu Al; Widyawati, Diah (Cv. Syntax Corporation Indonesia, 2025)
Economic resilience is a discourse in economics that will not stop. Each country and region that is part of it will ensure sufficient economic resilience capabilities. This is related to economic conditions that cannot be predicted with certainty. When economic conditions are shaken, a country that has better resilience tends to be able to survive. Economic activity is one of the essential keys to sustaining economic resilience from shocks. The industrial structure is a reflection of economic activity. Therefore, this study aims to map Indonesia's economic resilience based on regional distribution and empirically analyze the effect of diversification and specialization industrial structures on economic resilience from 1997 to 2015. The samples tested are from 25 provinces. Empirical analysis of the effect of industrial diversification structure and specialization on economic resilience in this study only covers the manufacturing industry using Large and Medium Industry Data. The estimation test applied is a static panel with a fixed effect model. The results of this study indicate that first, there are differences in conditions of resistance and recovery in regional economic resilience. The average regional resistance is above national conditions, while the average regional recovery is below national conditions. Second, specialization in the manufacturing industry positively affects regional economic resilience. Third, the diversification of the manufacturing industry sub-sector significantly negatively affects regional economic resilience.